2015
DOI: 10.1590/0004-282x20150202
|View full text |Cite
|
Sign up to set email alerts
|

Brief Cognitive Screening Battery (BCSB) is a very useful tool for diagnosis of probable mild Alzheimer´s disease in a geriatric clinic

Abstract: The diagnosis of early signs of Alzheimer’s disease (AD) is a major challenge in a heterogeneous population. Objective To investigate the use of the Brief Cognitive Screening Battery (BCSB) for the diagnosis of mild AD in a geriatric outpatient unit of a public hospital in the city of Rio de Janeiro. Method BCSB was administered to 51 elderly adults with a clinical diagnosis of probable AD and 123 older adults without dementia (non-AD). Results AD patients performed worse than non-AD group in all BCSB te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
19
1
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 17 publications
5
19
1
4
Order By: Relevance
“…Eligible subjects completed the Consortium to Establish a Registry for Alzheimer's disease neuropsychological battery (CERAD) and the Brief Cognitive Screening Battery (BCSB), as well as the World Health Organization Disability Assessment Schedule with 36 items (WHODAS). We then used validated Brazilian cut‐points to establish the presence of memory impairment (CERAD word list recall <3 or delay memory of the BCSB <5), impaired fluency (1‐minute list yielding <9 animals), impaired naming (Boston naming test score <12), impaired clock drawing (score <3), or impaired constructional praxis (CERAD subscore <9) . Impaired social or occupational function was defined by a WHODAS score >40…”
Section: Methodsmentioning
confidence: 84%
“…Eligible subjects completed the Consortium to Establish a Registry for Alzheimer's disease neuropsychological battery (CERAD) and the Brief Cognitive Screening Battery (BCSB), as well as the World Health Organization Disability Assessment Schedule with 36 items (WHODAS). We then used validated Brazilian cut‐points to establish the presence of memory impairment (CERAD word list recall <3 or delay memory of the BCSB <5), impaired fluency (1‐minute list yielding <9 animals), impaired naming (Boston naming test score <12), impaired clock drawing (score <3), or impaired constructional praxis (CERAD subscore <9) . Impaired social or occupational function was defined by a WHODAS score >40…”
Section: Methodsmentioning
confidence: 84%
“…However, the authors acknowledged that their findings might not be representative of other regions in Brazil, as the sample came from a private clinic in a city with a high human development index. In fact, other Brazilian studies have suggested that the Clock Drawing Test may have limited diagnostic ability for AD 24 or dementia 46 diagnoses in the context of low education.…”
Section: Discussionmentioning
confidence: 97%
“…It includes the Figure Memory Test, the Clock Drawing Test and Verbal Fluency animal category. Fichman-Charchat et al 24 documented that each component contributed to the AD diagnosis, in a clinical sample that had heterogeneous clinical, cognitive and demographic characteristics, reflecting the context of several outpatient clinics in low income countries. In this study the Verbal Fluency and the Clock Drawing Test were significantly affected by education and had a lower diagnostic accuracy 24 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations